Evaluation of antioxidant activity, total phenolics, total flavonoids and LC–MS/MS characterisation of phenolic constituents in Stachys lavandulifolia. Issue 3 (1st February 2017) - Rahimi Khoigani, Soroush; Rajaei, Ahmad; Goli, Sayed Amir Hossein
Abstract: The aim of this study was to evaluate phenolics profile and antioxidant activity of Stachys lavandulifolia. Total phenolics (TP), total flavonoids (TF), DPPH assay (IC50), ferric ion reducing antioxidant power (FRAP) and total antioxidant capacity (TAC) of the methanolic extract were measured. The content of TP, TF, IC50, FRAP and TAC, were obtained as 16.59 gallic acid equiv./g dry matter (DM), 4.48 mg quercetin equiv./g DM, 2.07 (μg/mL), 0.014 (absorbance/mg phenolic) and 14.61 (mg BHT equiv./g DM), respectively. The results showed that S. lavandulifolia, compared to other species of Stachys, had moderate TP content with desirable antioxidant activity. Subsequently, 59 various phenolic compounds were identified and confirmed in the methanolic extract of S. lavandulifolia using high mass accuracy by MS2 experiments. The compounds consisted of 6 hydroxybenzoic acids and hydroxybenzoic aldehydes, 9 hydroxycinnamic acids, 1 coumarin, 32 flavonoids, 3 lignans, 2 stilbenes, 3 tannins and 3 other phenolics. Abstract :